Effective use of pre-exposure prophylaxis (PrEP) Among stimulant users with multiple condomless sex partners: a longitudinal study of men who have sex with men in Los Angeles. Issue 10 (3rd October 2019) - Goodman-Meza, David; Beymer, Matthew R.; Kofron, Ryan M.; Amico, K. Rivet; Psaros, Christina; Bushman, Lane R.; Anderson, Peter L.; Bolan, Robert; Jordan, Wilbert C.; Rooney, James F.; Wohl, Amy R.; Landovitz, Raphael J.
ABSTRACT: PrEP's potential benefit for men who have sex with men (MSM) who use stimulants may be limited by adherence or prescriber willingness to recommend PrEP due to concerns of non-compliance. Using data from PATH-PrEP, a 48-week study evaluating PrEP for MSM in Los Angeles, we modeled an interaction between stimulant use and condomless sex with multiple partners (CAS-MP) on prevention-effective dried blood spot tenofovir-diphosphate concentrations. At week 4, participants reporting stimulant use and CAS-MP had a decreased odds of prevention-effective adherence compared to non-stimulant use and non-CAS-MP (AOR 0.15, 95% CI 0.04–0.57). From week 4–48, participants reporting stimulant use and CAS-MP had increased odds of prevention-effective adherence (AOR 1.06 per week, 95%CI 1.01–1.12). Participants reporting CAS-MP without stimulant use had no significant change in prevention-effective adherence (AOR 0.99 per week, 95%CI 0.96–1.02). Stimulant use moderated the association of CAS-MP on prevention-effective PrEP adherence over time.